2005
DOI: 10.1007/s00244-004-0208-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organochlorine Compounds in Human Breast Milk from Mothers Living in Penang and Kedah, Malaysia

Abstract: This study determined the concentrations of polychlorinated dibenzo-p-dioxins/dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs), organochlorine (OC) pesticides, and tris(4-chlorophenyl) methane (TCPMe) in human breast milk samples collected in 2003 from primipara mothers living in Penang, Malaysia. OCs were detected in all the samples analyzed with DDTs, hexachlorocyclohexane isomers (HCHs), and PCBs as the major contaminants followed by chlordane compounds (CHLs), hexachlorobenzene (HCB), and TCPMe. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 42 publications
3
15
0
1
Order By: Relevance
“…Ratio of DDT metabolites over parent compound is often applies to identify their emission behavior (Schwarzbauer et al, 2003). The presence of p,p'-DDE in sediment and in animal samples in the present study supported that this metabolite is the main degradation product of DDT which is also in line with the earlier investigations (Monirith et al, 2000;Boonyatumanond et al, 2002;Sudaryanto et al, 2005;Bayen et al, 2003).…”
Section: Persistent Organic Pollutants (Pops)supporting
confidence: 92%
“…Ratio of DDT metabolites over parent compound is often applies to identify their emission behavior (Schwarzbauer et al, 2003). The presence of p,p'-DDE in sediment and in animal samples in the present study supported that this metabolite is the main degradation product of DDT which is also in line with the earlier investigations (Monirith et al, 2000;Boonyatumanond et al, 2002;Sudaryanto et al, 2005;Bayen et al, 2003).…”
Section: Persistent Organic Pollutants (Pops)supporting
confidence: 92%
“…6 Malez ya' da ya pı lan bir ça lış ma da; an ne özel lik le ri ile OKP ara sın da an lam lı bir iliş ki bu lun ma dı ğı be lirtil mek te dir. 20 Ben zer ola rak ça lış ma mız da da an nenin sos yo-de mog ra fik özel lik le ri ile an ne sü tün de sap ta nan OKP ara sın da her han gi bir iliş ki bu lunma mak ta dır.…”
Section: Tar Tiş Maunclassified
“…In some developing country, the use of OCPs had not been prohibited until recently, this may attribute in higher concentrations of OCPs. 6,7) Abballe et al reported that the milk from the mothers in Venice, Italy (industrial area) had PCOCs greater than those from the mothers in Rome, Italy (urban area). 8) Zhao et al reported that the concentrations of PCBs in milk from the mothers in Luqiao, China (industrial waste disposal area) were higher than those in Pingqiao, China (agricultural area).…”
Section: Polychlorinated Organic Compoundsmentioning
confidence: 99%